Maternal outcome in pregnant women with anaemia (Bangladesh Journal of Medical Science, 2018)
Background: Anaemia in pregnancy is one of the most important and common public health problem not only in India but also in most of the South East Asian countries. Anaemia is the most common nutritional deficiency disorder in the world. There is predominance of iron deficiency anaemia (nutritional anaemia). In pregnancy, it is one of the leading causes responsible for maternal morbidity and mortality.Objective: To find out the maternal outcome in pregnant women with anaemia at MMIMSR during the study period with special reference to the severity of the disease.Methods: The study was conducted in Department of Obstetrics and Gynaecology, MMIMSR, Mullana, Ambala(India). The study was carried out between the period of october 2012 to September 2014.A total of 200 cases of moderate and severe anaemia were included in the study on the basis of simple random sampling method and 200 cases of non anaemic subjects were included to serve as controls for the anaemic group, during the study period. Hb gm/dl was taken as criteria for deciding anaemia cases and also to classify them according to the severity. Cases were classified according to WHO criteria.Results: Out of 200 cases of anaemia, 70% were moderately anaemic (Hb 7 – 9.9gm/dl) and 30% were severly anaemic (Hb < 7gm/dl). Microcytic hypochromic type of anaemia (82.5%) was more prevalent suggesting nutritional inadequacies as cause of anaemia. Higher incidence of preterm (17%), PPH (7.5%), maternal morbidity (14.5%) was found in anaemic group as compared to non anaemic controls.Conclusion: Anaemia in pregnancy has adverse maternal outcome in the form of maternal morbidity, preterm labour, and increased incidence of operative delivery.Bangladesh Journal of Medical Science Vol.17(3) 2018 p.446-454